Inclusion of Nano-Fillers in Natural Fiber-Reinforced Polymer Composites Overviews and Applications - Asyraf M.R.M.; Hassan S.A.; Ilyas R.A.; Hazrati K.Z.; Syamsir A.; Zaki M.A.F.M.; Tee L.Y.; Vui Sheng D.D.C.; Nurazzi N.M.; Norrrahim M.N.F.; Rafidah M.; Rashedi A.; et al. (CRC Press, 2024)
Nanomaterial-based composites have been well-known due to their intrinsic properties toward advanced applications. Lignocellulosic fiber-reinforced polymer composites are usually hybridized with nano-fillers which establish a perspective class of polymer nanocomposites. Currently, the global communities are progressing in the development of promising class polymeric materials such as biocomposites, nano-filled polymer blends and bionanocomposites. Many researches and applications are continuously advanced to employ the bionanocomposites especially nanofiller/lignocellulosic fiber- reinforced polymer composites in many industrial sectors. These sectors are including defense, automotives, marine, packaging and domestic products. Hence, this chapter aims to provide a state-of-art review of the overview and background of lignocellulosic fiber with its polymer composites and the potential to be filled with nanoparticles. Most literatures fundamentally highlight that the incorporation of nanoparticles elevates composites strength, stiffness and provides thermal stability which is practical for many applications. Thus, the applications in major industrial sectors such as packaging, automotive and outdoor products are explained with the recent findings by other researchers. 2024 selection and editorial matter, N. M. Nurazzi, E. Bayraktar, M. N. F. Norrrahim, H. A. Aisyah, N. Abdullah, and M. R. M. Asyraf